Safety And Security Aid-Tool Of E-Hailing Drivers - Muhammad Nur Yusaidil, Yusmadi (2025)
Technological development of the facilities has placed the e-hailing services as one of the most unique modes of passenger transport. However, this rapid growth has also added several safety and security risks for e-hailing drivers including, driver predatory behaviour, employee sexual harassment or assault, charging customers more than the fare price and the risk of facing severe risks such as robberies or hijackings while on duty. While people’s demand for communication on e-hailing services has risen, the safety of drivers remains at risk as employment structures to tackle those challenges are missing. Due to this realization, the current study aimed at creating a Safety and Security Aid-tool for e-hailing drivers based on the Haddon Matrix. This article aims to establish the understanding of the main framework to deal with the safety and security issues, develop the tool from the identified framework and evaluate the tool for usability and efficiency. The tool was utilized in Microsoft Access, and risk management at an event was categorically divided into pre-event, during-event and post-event phases to manage these risks systematically. Credibility was evaluated with System Usability Scale (SUS) the result of which amounts to 75 points, that is worthy of ‘Good’ mark and high rate in terms of usability. For instance, in Case Study 1, the recorded score was 70% prescriptive of the acceptable threshold in usability, Case Study 2 was, however, recorded higher at 80% in acceptance, and usability. From the study, it was realised that although the tool was positively welcomed by the participants, there was still room for improvement in these areas as follows.There should be simplification of the interface, development and implementation of effective training programs and enhancement of feedback systems. These improvements will, lifts the usage and the level of acceptance with enhanced versatility into other arenas. Consequently, the proposed tool can be useful to solve safety and security issues of e-hailing drivers and will benefit the development of e-hailing services.